Diagnóstico do gerenciamento dos resíduos sólidos de serviços de saúde nos estabelecimentos veterinários de Mossoró-RN - Pereira, Cyntia Danielle da Silva (2014)
The Waste Health Services (RSS) are those outcomes of care to human or animal health, generated in hospital, clinics, laboratories, pharmacies and similar services and deserve attention because of potential risk to human health can offer as much for the environment. Inferred from the legislation that among the institutions responsible for managing RSS from its generation to final disposal, are those of veterinary care and veterinary clinics and pet shops, which has generated concern to health authorities the disposal of its waste, because improper disposal of some items endangers the health of pets and people in general. In this context the research aimed to evaluate the management of Solid Waste Health Services of veterinary establishments in the town of Mossoró-RN. Were selected 21 establishments were selected of veterinary clinics and pet stores of this municipality, which underwent an interview about the management of RSS based on CONAMA and ANVISA the resolutions, which govern the subject. Furthermore, the identification and quantification of RSS and guidance to those outlets about the risks of RSS and its management steps were performed. The descriptive data were from the notes made in the field daily, on the identification and quantification of waste produced and guidance to establishments obtained during the visits. The data obtained from the interviews were analyzed statistically, using the non-parametric test, Fisher exact, to compare the ratio of the group of veterinary clinic and pet shop. It was found that these stores generate RSS approximately 34kg/dia and destined to the landfill in the municipality without any form of treatment. These establishments not adequately perform the steps of waste management since the segregation until the final destination and that approximately 44% did not practice segregation and packaging as per the guidelines suggested by this study. We conclude that it is necessary to adopt measures of action to guide owners and responsible for veterinary establishments as their responsibility to RSS generator, as it is essential that the responsible agencies conduct surveillance veterinary care facilities so they look fit legislation and therefore fulfill its responsibility to RSS generator